Non-Unique Numerical Solutions in Visco-Plasticity - Antúnez, H.J. (Engineering Transactions, 1992)
We present the numerical analysis of a series of cutting problems for a visco-plastic material. The model is implemented in a finite element program written in the flow formulation framework. Almost ideal plasticity is achieved as the limit case of a visco-plastic material. Solution dependence on the chosen initial configuration (the final one being not known) suggests non-uniqueness inherent to the visco-plastic material with free surfaces, since a residual rate dependence is conserved in the model.